Konstruksi Makna Pertemuan Prabowo dan Surya Paloh Pasca Pengumuman Hasil Pilpres 2024 dalam Framing Media Online - Febriana, Poppy; Chusna, Rahma (PERSPEKTIF, 2024)
This article aims to reveal and analyze how online media (Mediaindonesia.com and Tempo.com) construct news coverage on the meeting between Prabowo and Surya Paloh following the announcement of the 2024 election results. The focus of this study is to identify the political orientation within the coverage and the framing used by each media outlet. The analysis applies Robert N. Entman’s Framing model, allowing researchers to understand the specific aspects highlighted by the media and how the events are narrated according to certain agendas. Data were collected through observation of news portals, using indicators such as news headlines and sources, with sample selection based on the research topic and qualitative analysis. The findings indicate that Mediaindonesia.com tends to emphasize positive aspects of Surya Paloh, highlighting the personal relationship between Paloh and Prabowo and Paloh’s mature stance on the election results, suggesting the influence of the media owner's interests. In contrast, Tempo.com focuses more on issues not covered by Mediaindonesia.com, particularly on the impact and dynamics resulting from the meeting. The implications of this study underline the importance of media independence in maintaining objectivity in political reporting and recommend greater transparency in news framing to avoid bias that may unfairly shape public opinion.